Limited occurrence of resistant radish (Raphanus sativus) to AHAS-inhibiting herbicides in Argentina - Pandolfo, Claudio Ezequiel (2013)
Radish has developed feral and weedy biotypes, which is a concern for agriculture around the world. In Argentina, it is one of the most widespread and troublesome crop weeds. In Brazil, this species has developed herbicide-resistance to acetohydroxyacid synthase (AHAS) inhibiting herbicides. The objective of this study was to record the presence of herbicide-resistant weedy radish plants in Argentina. In spring 2008, we found a small population of radish at the end of the flowering stage in an imidazolinone-tolerant canola field treated with imazethapyr. Screening and dose-response tests were conducted to two successive generations. They proved the biotype resistant status, and showed extensive survival (between 50 and 80% of control) to the application of a double dose of four AHAS‑inhibiting herbicides from two different chemical families (imidazolinones and sulfonylureas). Dose-response assays exhibited very high resistance for imazethapyr (LD50 = 2452.5 g a.i. ha-1, GR50 = 2926.9 g a.i. ha-1) and intermediate for metsulfuron (LD50 = 3.0 g a.i. ha-1, GR50 = 43.2 g a.i. ha-1). The acquisition of cross-resistance to different herbicide families would confer an adaptive and invasive advantage in agricultural environments to this biotype. Due to the herbicide rotation conducted in the field, the dispersion of this biotype was restricted. This is the first report of resistance in weedy radish in Argentina.